Product selection for a startup animal health company - Dunn, Ryan N. (Kansas State University, 2015)
Most corporations seem geared to buy assets, not sell them. Estimates suggest corporations acquire three businesses for every one they divest (Mankins 2008). A corporation with a disciplined approach to divestiture seems more likely to sharpen strategic focus and deliver value to shareholders. This thesis defines and explores the concept of an orphan product as an opportunity for divestiture from a parent company and subsequent acquisition for a startup company. Orphan product is defined by reviewing literature and selecting the following criteria for a given product; the product has a lack of marketing support/focus, the product is not considered core to the parent company, product sales trend over a 5-year time frame is decreasing, cash flows are uncertain, market growth for the category the product competes in is smaller than the industry average, the product life cycle position is mature, and portfolio synergy is low due to the parent company having other products that deliver similar benefits. A scorecard is developed and used to score orphan characteristics of four products in the animal health industry. Two of the four products analyzed are classified as orphan products and therefore potential candidates for purchase by the startup company. A Strategy Canvas is developed and value curves are assigned per product to show how the startup company can market an acquired product relative to the critical success factors in the animal health industry (Kim and Mauborgne, 2005). A framework of critical questions is posed to each product resulting in recommendations for the startup on critical success factors to eliminate, reduce, raise, or create. For the orphan products, a recommendations include: raise price, increase marketing support, and/or create new factors to differentiate such as to offer additional services or to develop pricing models that are simple and clear. Application of this research can be applied to companies seeking to acquire animal health products that would like to better understand how to improve their chances for success.
Keywords: Orphan Products; Blue Ocean; Animal Health; Strategy Canvas; Value Curve; Business (0310); Economics (0501); Economics, Agricultural (0503)